More Reading Power - Beatrice S.Mikulacky, Linda Jeffries (Longman, 2004)
More Reading Power, second edition, is a student-centered reading skills textbook based on a cognitive skills approach. Its four key sectionc, designed to be used concurrently , help intermediate to high-intermediate students develop solid reading skills necessary in school, collage , or business.